ANALYSIS OF THE COMPETENCY AND QUALITY OF STATE ORGANIZATION SERVICE MANAGEMENT ON THE LEVEL OF SATISFACTION OF THE FAKFAK DISTRICT COMMUNITY (Review of the Managerial Credibility of the Wagom Village Apparatus) - Nurasfa Isawati Iha; Choirul Anam; Putri Rahma Dayanti; Christina Wulansari (Sean Institute, 2023)
The readiness of the apparatus as the front guard element of state administration in the field of public services can be seen from the level of competence and quality of management in carrying out their functions. The research aims to understand the extent of the level of competency and quality of management on the level of satisfaction with the results of services by state civil servants to the people of Wagom sub-district, Pariwari district, Fakfak district. The research was carried out for 4 months in 2023 using a survey approach and interviews using closed questionnaires. The survey and interview results were processed quantitatively using the SPSS 2.3 statistical tool and described using spider web diagram analysis tools and gap value graphs. Research conclusions containing the substance of corrective actions are described using an Ishikawa diagram analysis approach with a combination of weighting.